Transforming floundering into success. Issue 2 (30th October 2012) - NAISH, LEE
Abstract: We show how logic programs with "delays" can be transformed to programs without delays in a way that preserves information concerning floundering (also known as deadlock). This allows a declarative (model-theoretic), bottom-up or goal-independent approach to be used for analysis and debugging of properties related to floundering. We rely on some previously introduced restrictions on delay primitives and a key observation which allows properties such as groundness to be analysed by approximating the (ground) success set.